Peningkatan keaktifan belajar siswa melalui model TGT pada pembelajaran matematika Kelas V Sekolah Dasar - Vidna Dea Permana; Victa Sari Dwi Kurniati; Diana Nyoman Sartika (Indonesian Journal of Learning and Educational Studies, 2024)
The low learning activity of fifth grade students in mathematics learning, which affects their learning outcomes. Increasing this learning activity is important to study because student activity in the learning process plays a significant role in improving their understanding and learning completion. This study aims to improve the learning activity of fifth grade students in mathematics learning through the Teams Games Tournament (TGT) learning model at SDN Rejowinangun 1. This type of research is Classroom Action Research with the Kemmis & MC Taggart Model consisting of the planning, implementation & Observation, and reflection stages. The research was conducted in 2 cycles, each consisting of 2 meetings. The subjects of this study were 28 fifth grade students of SDN Rejowinangun 1. The instrument used was an observation sheet. The data analysis techniques used were descriptive qualitative and quantitative. Student learning activity in Mathematics learning is said to be successful if ≥75% of the number of students are included in the minimum high category. The application of the Teams Games Tournament learning model shows an increase in the remaining learning activity in mathematics lessons. This is proven by the success rate of the action of 79% (22 students) in cycle II.